Transflective liquid crystal display using regular flat square electrodes. Issue 12 (25th September 2020) - Tian, Li-Lan; Chu, Fan; Li, Rui; Zhou, Xiang-Yu; Gu, Xiao-Qing; Li, Lei; Wang, Qiong-Hua; Deng, Huan
ABSTRACT: A single-cell-gap vertical alignment transflective liquid crystal display with flat square indium tin oxide electrodes is proposed. The proposed structure makes the best of the intrinsic fringe electric field between the flat square electrodes in each pixel to control the liquid crystal directors to match the optical path difference between the transmissive and reflective regions. Simulation results show that the display exhibits a reasonably high contrast ratio, low operating voltage, and symmetrical viewing angle. Moreover, the voltage-dependent transmittance and reflectance curves overlap well, which enables a single gamma curve driving. Graphical Abstract: uf0001